2009
DOI: 10.1186/1471-2334-9-196
|View full text |Cite
|
Sign up to set email alerts
|

Let the sun shine in: effects of ultraviolet radiation on invasive pneumococcal disease risk in Philadelphia, Pennsylvania

Abstract: BackgroundStreptococcus pneumoniae is a common cause of community acquired pneumonia and bacteremia. Excess wintertime mortality related to pneumonia has been noted for over a century, but the seasonality of invasive pneumococcal disease (IPD) has been described relatively recently and is poorly understood. Improved understanding of environmental influence on disease seasonality has taken on new urgency due to global climate change.MethodsWe evaluated 602 cases of IPD reported in Philadelphia County, Pennsylva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 35 publications
4
57
0
1
Order By: Relevance
“…Increased ambient UV radiation could act to reduce pathogen survival in the environment, as has been suggested previously 16 . Time spent indoors may be reduced on sunny days in our study setting, potentially limiting crowding and exposure to indoor smoke, both known risk factors for lower respiratory infections 23 .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Increased ambient UV radiation could act to reduce pathogen survival in the environment, as has been suggested previously 16 . Time spent indoors may be reduced on sunny days in our study setting, potentially limiting crowding and exposure to indoor smoke, both known risk factors for lower respiratory infections 23 .…”
Section: Discussionmentioning
confidence: 69%
“…Increased relative humidity was associated with increased IPD incidence in New Zealand, but not in Australia 12, 13 . Low sunlight and temperature are consistently associated with high pneumonia incidence in time series studies in temperate settings, where annual peaks of lower respiratory infections occur during the short days of winter 10,[12][13][14][15][16] . The association between temperature and respiratory infections in children is inconsistent in time series studies from tropical settings, suggesting temperature is unlikely to be an important driver of pneumonia incidence in the tropics [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virulence of the pathogen and the efficacy of host immune function boosted by 1,25-D 3 may determine the outcomes of invasive disease. 100 A doubleblind individually randomized placebo-controlled trial involving young children in an inner-city hospital in Kabul showed that the risk of a repeat episode of pneumonia within 90 days of supplementation of oral 100,000 IU of vitamin D 3 was lower in the intervention than in the placebo group. 101 Bahr et al examined group A streptococcal infections and found a striking association between vitamin D-binding protein (Gc2) and rheumatic fever in a homogeneous Arab population.…”
Section: Antimicrobial Efficacy Against Different Infective Agentsmentioning
confidence: 99%
“…Possible explanations of the seasonality seem to be the closer contact as a result of indoor crowding, lower humidity, induced variations in the human immune responses, indoor air pollution, low exposition to sunlight and ultraviolet (UV) radiation, keeping in mind the bactericidal effect of the latter [16]. In tropical regions, climate change also affects the pattern and seasonability of infections.…”
Section: Introductionmentioning
confidence: 99%